Sustainable Management of the Eastern Baltic Cod Fishery - Röckmann, Christine (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2006)
The present dissertation aims to shed light on the environmental / ecological, economic, and legal sides of fisheries management in the Baltic Sea with the objective to support the recovery of the Eastern Baltic cod stock and to contribute to the sustainable management of the Eastern Baltic cod fishery. A central question motivating this research is: Can a Marine Protected Area, permanent or seasonal, be effective in rebuilding the Eastern Baltic cod stock AND, at the same time, ensure future harvests to fishermen – also in light of global climate change? Several gaps towards a bio-economic evaluation of selected management policies for the Eastern Baltic cod fishery are bridged by this study. First, the legal framework of fisheries management at the European level, and particularly that of the Baltic Sea, is depicted (Chapter 2). The subsequent modelling-based policy analysis is designed to fit into this framework and to propose new legislation or policy recommendations. The core of the thesis is the development of a spatially explicit simulation model of the Eastern Baltic cod population dynamics (Chapter 3) and the subsequent coupling with economic calculations (Chapters 4 and 5). The population dynamics are externally driven by (a) management policies and (b) environmental scenarios. The simulations focus on the evaluation of an MPA as a management tool. The model is extended to incorporate global climate change and its regional consequences in the Baltic Sea area (Chapter 4). The driving question is whether stock recovery is possible in the face of global warming. A preliminary economic analysis is coupled to the biological component, allowing simulations of future yield and profit development. Finally, the economic model component is extended by calculating the variable costs of fishing (Chapter 5). Fishermen’s future operating profits are estimated, and a ranking of the selected management policies in terms of economic profit is suggested. The following conclusions can be drawn: A temporary marine reserve ...